Comparison of the clinical and prognostic characteristics of patients with different pathological types in acromegaly - Chong, Liye; Lou, Yuxing; Chen, Xue; Zhao, Wenji; Zhang, Wei; Zhang, Ziwei; Yang, Fan; Li, Ping (Frontiers in Endocrinology, 2025)
ContextAcromegaly is caused by somatotroph tumors. Recently, the WHO recommended the use of transcription factors (TFs) together with pituitary hormones to accurately classify the subtypes.ObjectiveThis study aims to evaluate differences in the clinical and prognostic characteristics of acromegaly patients with different pathological types.MethodsA retrospective study was conducted on 94 acromegaly patients who underwent surgical treatment. Patients were classified into two groups on the basis of TFs expression by IHC. PIT1 tumors were positive only for PIT1, and PIT1/SF1 tumors were positive for both PIT1 and SF1. Additionally, on the basis of the expression of GH and PRL by IHC, PIT1 tumors were further subdivided into GH positive tumors (those positive for only GH) and GH/PRL positive tumors (those positive for both GH and PRL). Differences in clinical and prognostic features among the pathological groups were evaluated.ResultsPIT1/SF1 tumors represented 30.9% (n = 29) of the acromegaly patients in this cohort. PIT1/SF1 tumors had a higher baseline IGF-1 index (2.77 ± 0.73 vs. 2.39 ± 0.74, P = 0.024) than PIT1 tumors. Despite the higher proportion of postoperative GH < 1 μg/L, the biochemical remission rate of PIT1/SF1 tumors (30.8% vs. 27.6%, P = 0.812) was similar to that of PIT1 tumors. Compared with those with GH positive tumors, patients with GH/PRL positive tumors were younger at diagnosis (42.50 ± 13.36 vs. 49.05 ± 11.69, P = 0.046), and the proportion of male patients was higher (50.0% vs. 23.3%, P = 0.048). Furthermore, patients with GH/PRL positive tumors had a significantly higher postoperative GH level [7.30 (3.18–11.08) vs. 2.49 (1.57–6.84), P = 0.011] and IGF-1 index (1.82 ± 0.94 vs. 1.31 ± 0.63, P = 0.011) during follow-up. The biochemical remission rate in GH/PRL positive tumors was lower, but the difference was not statistically significant (18.2% vs. 37.2%, P = 0.159).ConclusionPIT1/SF1 tumors represent approximately 30.0% of acromegaly patients. Despite higher baseline IGF-1 levels, the clinical and prognostic features of patients with PIT1/SF1 tumors are similar to those of patients with PIT1 tumors. GH/PRL positive tumors, characterized by their earlier age at diagnosis and male predominance, tend to exhibit a lower biochemical remission rate compared to GH positive tumors.